The timeless wisdom of Hinduism: Its impact on philosophy, ethics, and contemporary society - Sunkad, Gayatri (Yayasan Mitra Persada Nusantara, 2025)
Hinduism is considered the oldest religion in the world, predating even the Vedic civilization. Unlike other major religions with a specific founder—such as Prophet Muhammad for Islam or Jesus Christ for Christianity—Hinduism has no singular originator. Instead, it is often referred to as Sanatana Dharma, meaning